Needle-clipping of longleaf pine (Pinus palustris Mill.) can increase seedling survival while reducing transpiration and root growth potential - David B. South; Tom E. Starkey; D. Paul Jackson (Global Journal of Food and Agribusiness Management, 2019)
Clipping needles of longleaf pine (Pinus palustris Mill.) prior to transplanting has been shown to increase seedling survival but the mechanism for this effect is not well documented. A greenhouse trial was conducted to examine the effect of clipping needles on transpiration, root-growth potential (RGP) and seedling survival. Clipping longleaf pine needles to a length of 5 cm reduced transpiration and reduced RGP but it increased seedling survival by 34% points. Clipping to a length of 15 cm had an intermediate effect on these variables. The results support the common practice of clipping needles in the nursery.